Pengembangan Buku Pengayaan Menceritakan Kembali Legenda Rakyat Sragen yang Bermuatan Dimensi Gotong Royong Bagi Siswa SMP - Anggraini, Laras Widi; Zuliyanti, Zuliyanti (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to develop an enriching book retelling the legends of the Sragen people which contains the dimension of mutual cooperation. The basis of this research is the need for teachers and students for enrichment books to be used in learning activities to retell fantasy stories. The research method used in this research is the research and development method from Borg and Gall with five stages, namely 1) potential and problems, 2) data collection, 3) prototype design, 4) prototype validation, and 5) prototype revision. The results of the research show that the enrichment book retelling the Sragen folk legend which contains the dimension of mutual cooperation received an average score of 3.5 in the very good category so it is suitable for use by teachers and students in learning activities.